WEBINAR - Gupta, Gagan (SCHOOL SCIENCE, 2025)
During the COVID-19 pandemic in August 2021, the Department of Education in Science and Mathematics (DESM), National Council of Educational Research and Training (NCERT) had initiated an online live interactive sessions with experts from different fields titled ‘Webinar Series: Listening to Learn’ to provide an opportunity to learn about diverse issues related to the contemporary and relevant issues with the school education. These were telecast live on PMeVidya TV channels and NCERT Official YouTube channel. This short article provides the details of the interactions held till March 2022 for easy access of different stakeholders